Activism and Environmentalism in British Rock Music: the Case of Radiohead. - Guillaume Clément (Revue Française de Civilisation Britannique)
One of the most commercially and critically successful contemporary rock bands in Britain, Radiohead became famous for expanding their horizons beyond guitar-based rock music. In the course of their thirty-year career, as their music became more complex, Radiohead evolved into a politicized band as well, as singer and songwriter Thom Yorke found inspiration in the socio-political context of the time. While the songs of OK Computer (1997) offered a vision of British society at odds with the concept of Cool Britannia, later albums featured implicit criticisms aimed at the New Labour government. Moreover, Yorke often took to his band's official website in order to express his outrage at the British government's environmental policy, lending his support to organisations like Friends of the Earth and the Green Party. The analysis of some of Radiohead's best-known songs provides an outline of the band's political ideology, which was, in turn, fulfilled by some of the band members' activism. Radiohead can thus be defined as an activist band, not only due to the personal political commitment of some of the musicians, but also through their musical output, which provides a way for their audience to get acquainted with socio-political issues.